2019
DOI: 10.3390/antiox8080255
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Olive Leaf Extract (OLE) for Producing Fortified Fresh Pasteurized Milk with an Extended Shelf Life

Abstract: An olive leaf extract (OLE) has been tested in vitro for its antibacterial activity and ability to inhibit α-glucosidase enzyme. OLE was also evaluated for its potential, when added to pasteurized milk, to preserve nutritional parameters and to limit microbial growth, thus prolonging shelf life. In vitro assays demonstrated a strong antibacterial efficacy of OLE mainly against Bacillus cereus and the capacity to inhibit α-glucosidase enzyme (IC50) when used at 0.2 mg oleuropein/mL. The milk fortification with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…The HPLC results for the phenolic compounds of FLE were similar to the results reported by Nadeem and Zeb [68], who stated that caftaric acid, quercetin-3, 7-diglucoside, and quercetin-3-glucoside were the main phenolic compounds. The levels of phenolic compounds in OLE in the present study are consistent with those of Palmeri et al [9], who showed that all phenolic compounds in OLE classified as polyphenols. As widely presented in the literature; oleuropein was 90% of phenolic compounds, followed by ligstroside (1.12 mg/g dried extract) and luteolin 7-O-glucoside (0.81 mg/g dried extract).…”
Section: Characterization Of the Phenolic Compounds By Hplcsupporting
confidence: 93%
See 1 more Smart Citation
“…The HPLC results for the phenolic compounds of FLE were similar to the results reported by Nadeem and Zeb [68], who stated that caftaric acid, quercetin-3, 7-diglucoside, and quercetin-3-glucoside were the main phenolic compounds. The levels of phenolic compounds in OLE in the present study are consistent with those of Palmeri et al [9], who showed that all phenolic compounds in OLE classified as polyphenols. As widely presented in the literature; oleuropein was 90% of phenolic compounds, followed by ligstroside (1.12 mg/g dried extract) and luteolin 7-O-glucoside (0.81 mg/g dried extract).…”
Section: Characterization Of the Phenolic Compounds By Hplcsupporting
confidence: 93%
“…On the other hand, this procedure causes a significant loss of the flavor, color, several vitamins, and antimicrobial compounds [6][7][8]. However, pasteurized milk is a high-nutritional-value product, but with a limited shelf life (only 5-7 days) at 5-8 • C, and it is costly compared with UHT milk [9]. The pasteurization techniques of milk are divided into two common types, according to the Codex Alimentarius [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have proposed the enrichment of different food products with an olive leaf phenolic extract (OLE), as in the case of vegetable oils, due to their antioxidant activity (i.e., sunflower, soybean, maize, and frying oils) [2], or meat products against oxidative [3] and microbial spoilage [4]. Moreover, the use of OLE was also tested in cereal [5] and dairy products [6]. Apart from having healthy, antioxidant, and antimicrobial properties, olive polyphenols have been proven to exert important technological functionality, such as a water/oil holding capacity and emulsifying activity [7], and can represent a useful multifunctional ingredient that can help in the production and stabilization of complex food products such as emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Its contribution on shelf life and chemical and sensory characteristics of stracciatella is still unknown. OLE has been recently tested for antimicrobial activity based on the high polyphenols content [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%